42 Screening for Atrial Fibrillation in Housebound Individuals: An Evaluation of the Use of the AliveCor Kardia Device. (6th February 2020) - Bell, C; Heitz, E
Abstract: Background: The Croydon Rapid Response service is a multidisciplinary team providing admission avoidance support for people at crisis in their own homes or care homes. This population includes many living with frailty, the majority of whom are housebound. Introduction: Atrial fibrillation (AF) is common, and often asymptomatic, and a significant risk factor for developing an ischaemic stroke. There is an ambition across health systems to improve identification of people with AF to better manage their risk of stroke. Screening is often performed using ECG readings typically performed in healthcare settings such as GP surgeries or hospitals. The Croydon Rapid Response Team were provided with 10 AliveCor Kardia devices as part of a programme funded by the Health Innovation Network, with the aim to screen for AF aiming in traditionally hard-to-reach populations such as those people who are, through ill health or poor mobility, unable to leave their own home. Methods: Activity use of the AliveCor Kardia devices were collated from centralised activity data based on the device serial numbers. Data collected were reviewed over a 12 month period. After 12 months use a survey was performed of clinician's views on the devices. Results: Over a 12 month period (March 2018 – February 2019) 389 recordings were performed across all Kardia devices. One device was lost within 1 month of the roll-out. Of the 389 recordings performed, possible AF was identified in 56 cases (14% of those screened). Survey results were received from 6 clinicians. 1 clinician used the device everyday in their practice. 2 staff members report using it 1-2/week, 3 staff members report using it 1-2/month. 100% of respondents described the device as easy to use and helpful in clinical practice. 100% of respondents agreed that they were clear how to manage a positive result. None of the respondents described increased workload due to the device and screening programme. Conclusions: The AliveCor Kardia device is an acceptable and effective tool to aid detection of AF in housebound individuals seen by the Rapid Response team. The scheme should be considered for extension to other community teams, and further diagnostic equipment such as 12 lead ECG should be considered to complete the pathway.